2017 IEEE/AIAA 36th Digital Avionics Systems Conference (DASC) 2017
DOI: 10.1109/dasc.2017.8102135
|View full text |Cite
|
Sign up to set email alerts
|

Placing LDACS-based ranging sources for robust RNP 1.0 accuracy en-route

Abstract: Global Navigation Satellite Systems (GNSS) are becoming the primary means of navigation for civil aviation. Nevertheless, concerns about GNSS outages remain, driving the need for Alternative Positioning, Navigation and Timing (APNT) systems to provide availability and continuity for performancebased navigation services. Although the existing Distance Measuring Equipment (DME) infrastructure is able to provide Required Navigation Performance (RNP) 1.0 accuracy, it is not robust for individual station outages. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In this paper we present a modified version of methodology proposed in [4], which can be used to assess the impact of the new technologies at horizon on legacy DME navigation system. The deployment of new raging signals make it possible to decommission older radio navigation solutions.…”
Section: Scope Of This Workmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper we present a modified version of methodology proposed in [4], which can be used to assess the impact of the new technologies at horizon on legacy DME navigation system. The deployment of new raging signals make it possible to decommission older radio navigation solutions.…”
Section: Scope Of This Workmentioning
confidence: 99%
“…In [4], we presented a optimization method to select sites from existing aeronautical navigation/communication network as potential locations for a new technology. We have shown that a hybridization of existing DME network with a better ranging system provides a robust RNP 1.0 accuracy over German airspace.…”
Section: Rationalization Strategymentioning
confidence: 99%
See 3 more Smart Citations